Experimental investigation of an optimized indirect free cooling system including a dry cooler equipped with evaporative cooling pads for data center - Hnayno, Mohamad; Chehade, Ali; Klaba, Henryk; Polidori, Guillaume; Maalouf, Chadi (Energy Reports, 2023)
Different heat rejection systems could be used to discharge the heat of liquid cooled data center to the ambience. The dry cooler as an indirect free cooling solution is one of the most used, where outside air is applied as a cooling fluid for its finned heat exchangers (FHEXs). In ambiences where dry coolers ambient temperatures are higher than supplied FHEX’s water temperature, evaporative cooling system can be used as pre-coolers. This paper presents an experimental investigation conducted on an indirect free cooling system including a dry cooler equipped with evaporative cooling pads (IFC+EC) under 20 K data center temperature difference for high outdoor conditions, variable fan speed, reduction in cooling pad’s surface and increasing in water supply temperature. The results show that the dry cooler is successfully operated under 20 K temperature difference. Furthermore, by increasing the air speed from 2 m/s to 3 m/s, the pads’ outlet air temperature increases by 0.6 K, the relative humidity tends to decrease about 9% and its efficiency decreases from 97% to 88%. Surface clogging had no significant impacts. A slight rise of 1.24 K in air outlet temperature and a decrease of about 3.3% and 2.5% in relative humidity and cooling pad thermal efficiency respectively were detected while increasing water supply temperature from 23 °C to 44 °C. This allowed authors to propose an optimized IFC+EC system with precooling DC supply water before the dry cooler to reduce its cooling demand by at least 31%.
Keywords: Data center cooling; Energy; Free cooling; Heat transfer; Liquid cooling